Preparation method and application of NiCoCu selenide composite MXene / carbon sphere film electrode material

By preparing NiCoCu selenide composite MXene/carbon spherical film electrode material, the problems of low energy density and MXene self-stacking of supercapacitors are solved, and high energy density and long cycle stability are achieved.

CN119517633AActive Publication Date: 2025-02-25JIANGSU UNIV

Patent Information

Application Number
CN202411650840.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-25
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

The energy density of existing supercapacitors is low, limiting their practical application, and MXene materials are prone to self-stack during cycles, resulting in a rapid decline in capacity.

Method used

NiCoCu selenide composite MXene/carbon ball film electrode material is prepared by hydrothermal method, solution method and high-temperature hydrothermal treatment, etc., to form NiCoCu-Se@MXene/CS composite film electrode material to avoid MXene self-stacking and improve the conductivity and structural stability of the material.

Benefits of technology

The energy density and power density of the supercapacitor are significantly improved, the cycle stability is extended, and the capacity retention rate reaches more than 82.4%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119517633A_ABST
    Figure CN119517633A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of composite electrode materials, and relates to a preparation method of a NiCoCu selenide composite MXene / carbon sphere thin film electrode material, which comprises the following steps: firstly, dissolving ZIF-67 powder in a carbon sphere solution, then adding an MXene aqueous solution, stirring for 1-10 hours, and carrying out suction filtration and drying to obtain ZIF-67 MXene / CS; secondly, a solution is prepared from urea, a copper source, a nickel source and ethyl alcohol according to the proportion, ZIF-67 (at) MXene / CS is immersed in the solution, and a NiCoCu-LDH (at) MXene / CS thin film is obtained after a hydrothermal reaction; and thirdly, mixing the NiCoCu-LDH-coated MXene / CS film, selenium powder and sodium borohydride according to a mass ratio of (0.5-1): (1-2): (1-2), reacting at 150-180 DEG C for 12-24 hours, washing the obtained product with deionized water, and drying to obtain the NiCoCu-LDH-coated MXene / CS composite material. The MXene and the carbon spheres jointly provide a flexible substrate for the self-supporting material, the conductivity and the specific surface area of the material are increased, meanwhile, NiCoCu-Se is intercalated into the MXene, an intermediate buffering effect is achieved, self-stacking of the MXene is prevented, and the structure of the self-supporting material is more stable. When the self-supporting material is applied to a positive electrode material of a supercapacitor, the self-supporting material avoids using an adhesive, so that the impedance of the material is reduced, and the electrochemical performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of composite electrode materials, relates to thin film electrodes, and in particular to a preparation method and application of a NiCoCu selenide composite MXene / carbon sphere thin film electrode material Background Art

[0002] With the deepening of global energy transformation and the continuous improvement of science and technology, the development of new renewable energy and high-efficiency electrochemical energy storage devices has also accelerated. As one of the electrochemical energy storage devices, supercapacitors have the characteristics of safety, stability, high power density, and fast charging and discharging speed, and have attracted widespread attention from scientists. However, due to the limited total number of electrolyte ions stored on the electrode surface, the overall energy density of supercapacitors has always been low, which has hindered the practical application of supercapacitors. Therefore, the rational design of electrode materials is the key to improving the energy density of supercapacitor electrode materials.

[0003] Combining transition metal selenides with excellent conductive materials (such as carbon materials or MXene) can not only improve the conductivity of the material, but also enhance the structural stability. Carbon spheres, as a type of carbon material, have high specific surface area, excellent conductivity, good chemical stability and mechanical strength, can remain stable in harsh electrochemical environments, and their morphology, porosity and composition are easy to adjust to meet different application requirements. MXene is a two-dimensional material prepared by etching away the A layer in the MAX phase, usually with the chemical formula M n+1 X n T x Indicated, where M represents an early transition metal, X is a C or N element, and T is a surface functional group (-F, -O or -OH has a unique two-dimensional structure), it has become a candidate material for supercapacitor electrode materials due to its unique structure and ion storage properties. It has a high specific surface area, adjustable functionalized surface ends, good conductivity and high electrochemical activity, making it very suitable as an electrode for supercapacitors. However, like other 2D materials, MXene materials are layered transition metal carbonitrides, which will inevitably restack during the cycle process, resulting in a significant and rapid decrease in capacity. To prevent MXene from self-stacking, other low-dimensional materials are introduced between the layers as spacer buffers, such as heterogeneous assembly of MXene with LDH to make their structure more stable. In addition, the effective combination of transition metal selenides with carbon materials and MXene can improve the conductivity and structural stability of the material, thereby significantly improving its electrochemical performance.

[0004] From the periodic table, we know that selenium (Se) belongs to the same main group as oxygen (O) and sulfur (S), and has similarities in some properties, but Se has better metallic properties and higher electrical conductivity (1×10 -3 S m-1 ), exceeding O and S (1×10 -5 S m -1 and 5×10 -28 S m -1 ). In addition, transition metal selenides (TMSe) have better rate performance and stability than transition metal oxides (TMO) and transition metal sulfides (TMS). Their excellent conductivity, rich valence state capabilities, good mechanical stability and thermal stability have attracted more and more attention in electronic devices, and have also been studied and applied in the fields of electronics and optics. Summary of the invention

[0005] In view of the deficiencies in the above-mentioned prior art, an object of the present invention is to disclose a preparation method and application of a NiCoCu selenide composite MXene / carbon sphere thin film electrode material.

[0006] Technical Solution

[0007] Glucose (C6H 12 O6), cobalt salt, 2-methylimidazole (C4H6N2), nickel salt, copper salt, urea (CO(NH2)2), sodium borohydride (NaBH4), selenium powder and titanium carbide aqueous solution (MXene, 4.5 mg / mL) were used as raw materials. Carbon spheres (CS) were first prepared by a hydrothermal method, ZIF-67 was prepared by a solution method, and then ZIF-67@MXene / CS material was obtained by a rapid chemical reaction method. Then NiCoCu-LDH@MXene / CS was prepared by a hydrothermal method, and finally it was subjected to high-temperature hydrothermal treatment to obtain NiCoCu-Se@MXene / CS thin film electrode material.

[0008] A method for preparing a NiCoCu selenide composite MXene / carbon sphere (NiCoCu-Se@MXene / CS) thin film electrode material comprises the following steps:

[0009] A. Dissolve ZIF-67 powder in carbon sphere solution, add MXene aqueous solution, stir for 1 to 10 hours, preferably 6 hours, filter and dry to obtain ZIF-67@MXene / CS; wherein the material ratio of ZIF-67 powder, carbon sphere solution and MXene aqueous solution is 10 to 80 mg: 10 to 30 mL: 2 to 10 mL, preferably 50 mg: 20 mL: 5 mL;

[0010] B. Prepare a solution according to the material ratio of urea, copper source, nickel source and ethanol of 0.1-0.6g:0.1-0.5mM:0.1-0.5mM:15-30mL, preferably 0.3g:0.3mM:0.3mM:20mL; immerse the above ZIF-67@MXene / CS, react at 100-120°C for 1-2h, preferably at 120°C for 2h, take out the reactor after it is naturally cooled to room temperature, wash it with deionized water and anhydrous ethanol several times, and dry it at 60°C to obtain a NiCoCu-LDH@MXene / CS film;

[0011] C. Mix NiCoCu-LDH@MXene / CS film, selenium powder and sodium borohydride in a mass ratio of 0.5-1:1-2:1-2, preferably 1:1:2, and heat in an autoclave at 150-180°C.

[0012] The reaction was carried out for 12 to 24 hours, preferably at 180° C. for 24 hours, and the obtained product was washed with deionized water and dried to obtain NiCoCu-Se@MXene / CS.

[0013] According to a preferred embodiment of the present invention, in step A, the ZIF-67 powder is prepared by mixing equal volumes of a cobalt salt-methanol solution and a 2-methylimidazole-methanol solution, stirring the mixture, centrifuging the mixture after standing for 24 hours, and drying the mixture at 60°C, wherein the cobalt salt is Co(NO3)2 or CoCl2; the cobalt salt-methanol solution is prepared by mixing cobalt salt and methanol at a ratio of 1 to 5 mmol:15 to 30 mL, preferably 3 mmol:20 mL; and the 2-methylimidazole-methanol solution is prepared by mixing 2-methylimidazole:methanol at a ratio of 0.820 to 2.46 g:15 to 30 mL, preferably 1.633 g:20 mL.

[0014] According to a preferred embodiment of the present invention, in step A, the carbon ball solution is prepared by dissolving the carbon source in deionized water at a ratio of 3-5 g:20-50 mL, preferably 4 g:40 mL, and hydrothermally reacting at 150-180° C. for 4-8 h, preferably at 160° C. for 6 h, and the carbon source is glucose.

[0015] In a preferred disclosed example of the present invention, in step A, the MXene aqueous solution is a titanium carbide aqueous solution with a concentration of 4.5 mg / mL.

[0016] According to a preferred embodiment of the present invention, in step B, the copper source is Cu(NO3)2 or CuSO4, preferably Cu(NO3)2; the nickel source is Ni(NO3)2 or NiCl2, preferably Ni(NO3)2.

[0017] According to the method of the present invention, the size of the prepared NiCoCu-Se@MXene / CS composite thin film electrode material can be arbitrarily cut according to actual conditions. It can be observed in a microscopic state that the NiCoCu-Se polyhedron is composited with MXene / CS, and the polyhedron appears hollow.

[0018] Another object of the present invention is to use the prepared NiCoCu-Se@MXene / CS composite thin film electrode material as a positive electrode material for a supercapacitor.

[0019] The prepared NiCoCu-Se@MXene / CS composite film electrode material was used as the positive electrode material at 6 mol L -1 The activated carbon, conductive carbon black and binder are uniformly mixed and dispersed in N-methylpyrrolidone solution at a mass ratio of 8:1:1, and then coated on nickel foam, dried and pressed into sheets to prepare electrode sheets as the negative electrode material of the capacitor. Electrochemical performance tests such as cyclic voltammetry (CV) and constant current charge and discharge (GCD) are carried out in a two-electrode system, and the corresponding energy density and power density are calculated to evaluate the electrochemical performance of the prepared NiCoCu-Se@MXene / CS composite thin film electrode material. The voltage range of the cyclic voltammetry (CV) test is 0-0.5V, and the scanning speed is 2, 5, 10, 20, 50 and 100mV s respectively. -1 The voltage range of the constant current charge and discharge test is 0-0.5V, and the current density is 1, 2, 3, 5, 8 and 10Ag. -1 .

[0020] The NiCoCu-Se@MXene / CS composite thin film electrode material prepared in the present invention is subjected to structural analysis and performance analysis using instruments such as a field emission scanning electron microscope (SEM), an X-ray diffractometer (XRD), and a CHI-760E electrochemical workstation to evaluate its electrochemical activity.

[0021] MXene has a unique two-dimensional structure, high specific surface area, adjustable functionalized surface ends, good conductivity and high electrochemical activity. Especially when combined with transition metal selenides, it can greatly enhance the electrochemical performance of the material.

[0022] The reactants and reagents used in the present invention are all commercially available, including glucose (C6H 12O6), cobalt nitrate hexahydrate (Co(NO3)2·6H2O), 2-methylimidazole (C4H6N2), nickel nitrate hexahydrate (Ni(NO3)2·6H2O), copper nitrate trihydrate (Cu(NO3)2·3H2O), urea (CO(NH2)2), sodium borohydride (NaBH4), selenium powder and titanium carbide aqueous solution (MXene, 4.5 mg / mL).

[0023] Beneficial Effects

[0024] The present invention synthesizes NiCoCu-Se@MXene / CS composite thin film electrode material through three steps: solution method, hydrothermal method and suction filtration method. MXene and carbon spheres together provide a flexible substrate for the self-supporting material, increase the conductivity and specific surface area of ​​the material, and at the same time, NiCoCu-Se is intercalated into MXene, playing an intermediate buffering role, preventing MXene from self-stacking, and making its structure more stable. In addition, when used as a positive electrode material for supercapacitors, the self-supporting material avoids the use of adhesives, reduces the impedance of the material, and greatly improves the electrochemical performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 .Scanning electron microscope image of the NiCoCu-Se@MXene / CS composite thin film electrode material prepared in Example 1;

[0026] Figure 2 .GCD curve of the NiCoCu-Se@MXene / CS composite thin film electrode material prepared in Example 1;

[0027] Figure 3 .Energy density-power density diagram of supercapacitor assembled with NiCoCu-Se@MXene / CS composite thin film electrode material prepared in Example 1;

[0028] Figure 4 .Cycling stability diagram of supercapacitor assembled with NiCoCu-Se@MXene / CS composite thin film electrode material prepared in Example 1. DETAILED DESCRIPTION

[0029] The present invention is described in detail below in conjunction with embodiment, so that those skilled in the art can better understand the present invention, but the present invention is not limited to the following examples. Unless otherwise limited, the terms used herein (including scientific and technological terms) should be interpreted as having the same meaning as commonly understood by those skilled in the art to which the present invention belongs. It will also be understood that the terms used herein should be interpreted as having a meaning consistent with their meanings in the content of this specification and the related art, and should not be interpreted in an idealized or excessive form, unless specifically so defined here.

[0030] Example 1

[0031] A method for preparing a NiCoCu selenide composite MXene / carbon sphere thin film electrode material comprises the following steps:

[0032] Step 1, weigh 3mmol Co(NO3)2·6H2O and 1.633g 2-methylimidazole and dissolve them in 20mL methanol respectively, mix the Co(NO3)2 methanol solution and the 2-methylimidazole solution and stir for 10 minutes, place at room temperature for 24 hours, centrifuge, and dry at 60°C to obtain ZIF-67 powder; weigh 4g glucose and dissolve it in 40mL deionized water, and hydrothermally react at 160°C for 6h to obtain a carbon ball solution; take 50mg of the above ZIF-67 powder and dissolve it in 20mL carbon ball solution, then add 5mL MXene aqueous solution, stir at room temperature for 6h, filter and dry to obtain ZIF-67@MXene / CS;

[0033] Step 2: Weigh 0.3 g CO(NH2)2, 0.3 mmol Cu(NO3)2·3H2O, and 0.3 mmol Ni(NO3)2·6H2O and dissolve them in 20 mL ethanol. Immerse the prepared ZIF-67@MXene / CS film in the above solution and react at 120°C for 2 h. After the reactor cools to room temperature, take out the sample, wash the sample with deionized water and anhydrous ethanol several times, and dry it at 60°C to obtain NiCoCu-LDH@MXene / CS film.

[0034] Step 3: Mix NiCoCu-LDH@MXene / CS, selenium powder and sodium borohydride in a mass ratio of 1:1:2 in an autoclave and react at 180°C for 24 hours. The obtained material is washed with deionized water and dried to obtain a NiCoCu-Se@MXene / CS composite thin film electrode material.

[0035] Characterization and analysis of NiCoCu-Se@MXene / CS composite thin film electrode materials

[0036] like Figure 1 As shown in the figure, it can be seen that in the microscopic state, NiCoCu-Se hollow polyhedrons are interspersed in MXene / CS to form a film-like structure with an ultra-high specific surface area.

[0037] like Figure 2 As shown in the figure, the GCD curve of NiCoCu-Se@MXene / CS composite film electrode material can be seen, and it can be calculated that the material has a current density of 1A. -1 At 1252.3F g -1 High specific capacity.

[0038] like Figure 3 As shown in the figure, the NiCoCu-Se@MXene / CS composite film electrode material prepared in this embodiment is used as a supercapacitor electrode material for the application of a two-electrode system. From the energy density-power density diagram, it can be seen that the assembled supercapacitor has good power density and energy density. When its power density is 800W kg -1 The maximum energy density that can be achieved is 108.3Wh kg -1 .

[0039] like Figure 4 As shown in the figure, the NiCoCu-Se@MXene / CS composite thin film electrode material prepared in this embodiment is used as the positive electrode material of the supercapacitor for cycle stability test results. After 10,000 cycles, the capacity retention rate is 82.4%, showing good cycle performance.

[0040] Example 2

[0041] A method for preparing a NiCoCu selenide composite MXene / carbon sphere thin film electrode material comprises the following steps:

[0042] Step 1, weigh 3mmol CoCl2·6H2O and 1.633g 2-methylimidazole and dissolve them in 20mL methanol respectively, mix the CoCl2 methanol solution and the 2-methylimidazole solution and stir for 10 minutes, place at room temperature for 24 hours, centrifuge, and dry at 60°C to obtain ZIF-67 powder; weigh 4g glucose and dissolve it in 40mL deionized water, and hydrothermally react at 160°C for 6h to obtain a carbon ball solution; take 50mg of the above ZIF-67 powder and dissolve it in 20mL carbon ball solution, then add 5mL MXene aqueous solution, stir at room temperature for 6h, filter and dry to obtain ZIF-67@MXene / CS;

[0043] Step 2: Weigh 0.3 g CO(NH2)2, 0.3 mmol CuSO4·5H2O, and 0.3 mmol NiCl2·6H2O and dissolve them in 20 mL ethanol. Immerse the prepared ZIF-67@MXene / CS film in the above solution and react at 120°C for 2 h. After the reactor is cooled to room temperature, take out the sample, wash the sample with deionized water and anhydrous ethanol several times, and dry it at 60°C to obtain NiCoCu-LDH@MXene / CS film.

[0044] Step 3: Mix NiCoCu-LDH@MXene / CS, selenium powder and sodium borohydride in a mass ratio of 1:1:2 in an autoclave and react at 180°C for 24 hours. The obtained material is washed with deionized water and dried to obtain a NiCoCu-Se@MXene / CS composite thin film electrode material.

[0045] The prepared NiCoCu-Se@MXene / CS composite thin film electrode material was used as the positive electrode material of the supercapacitor for a cycle stability test. The capacity retention rate was 80.8% after 10,000 cycles, showing good cycle performance.

[0046] Example 3

[0047] A method for preparing a NiCoCu selenide composite MXene / carbon sphere thin film electrode material comprises the following steps:

[0048] Step 1, weigh 1mmol Co(NO3)2·6H2O and 0.820g 2-methylimidazole and dissolve them in 15mL methanol respectively, mix the Co(NO3)2 methanol solution and the 2-methylimidazole solution and stir for 10 minutes, place them at room temperature for 24 hours, centrifuge them, and dry them at 60°C to obtain ZIF-67 powder; weigh 3g glucose and dissolve it in 20mL deionized water, and hydrothermally react at 150°C for 4h to obtain a carbon ball solution; take 10mg of the above ZIF-67 powder and dissolve it in 10mL carbon ball solution, then add 2mL MXene aqueous solution, stir at room temperature for 1h, filter and dry to obtain ZIF-67@MXene / CS;

[0049] Step 2, weigh 0.1g CO(NH2)2, 0.1mmol Cu(NO3)2·3H2O, 0.1mmol Ni(NO3)2·6H2O and dissolve them in 15mL ethanol, immerse the prepared ZIF-67@MXene / CS film in the above solution, and react at 120℃ for 2h; after the reactor is cooled to room temperature, take out the sample, wash the sample with deionized water and anhydrous ethanol several times, and dry it at 60℃ to obtain NiCoCu-LDH@MXene / CS film;

[0050] Step 3: Mix NiCoCu-LDH@MXene / CS, selenium powder and sodium borohydride in a mass ratio of 1:1:2 in an autoclave and react at 180°C for 24 hours. The obtained material is washed with deionized water and dried to obtain a NiCoCu-Se@MXene / CS composite thin film electrode material.

[0051] The prepared NiCoCu-Se@MXene / CS composite thin film electrode material was used as the positive electrode material of the supercapacitor for a cycle stability test. The capacity retention rate was 71.2% after 10,000 cycles, showing good cycle performance.

[0052] Example 4

[0053] A method for preparing a NiCoCu selenide composite MXene / carbon sphere thin film electrode material comprises the following steps:

[0054] Step 1, weigh 5mmol Co(NO3)2·6H2O and 2.46g 2-methylimidazole and dissolve them in 30mL methanol respectively, mix the Co(NO3)2 methanol solution and the 2-methylimidazole solution and stir for 10 minutes, place at room temperature for 24 hours, centrifuge, and dry at 60°C to obtain ZIF-67 powder; weigh 5g glucose and dissolve it in 50mL deionized water, and hydrothermally react at 180°C for 8h to obtain a carbon ball solution; take 80mg of the above ZIF-67 powder and dissolve it in 30mL carbon ball solution, then add 10mL MXene aqueous solution, stir at room temperature for 10h, filter and dry to obtain ZIF-67@MXene / CS;

[0055] Step 2, weigh 0.6g CO(NH2)2, 0.5mmol Cu(NO3)2·3H2O, 0.5mmol Ni(NO3)2·6H2O and dissolve them in 30mL ethanol, immerse the prepared ZIF-67@MXene / CS film in the above solution, and react at 120℃ for 2h; after the reactor is cooled to room temperature, take out the sample, wash the sample with deionized water and anhydrous ethanol several times, and dry it at 60℃ to obtain NiCoCu-LDH@MXene / CS film;

[0056] Step 3: Mix NiCoCu-LDH@MXene / CS, selenium powder and sodium borohydride in a mass ratio of 1:1:2 in an autoclave and react at 180°C for 24 hours. The obtained material is washed with deionized water and dried to obtain a NiCoCu-Se@MXene / CS composite thin film electrode material.

[0057] The prepared NiCoCu-Se@MXene / CS composite thin film electrode material was used as the positive electrode material of the supercapacitor for a cycle stability test. The capacity retention rate was 79.6% after 10,000 cycles, showing good cycle performance.

[0058] Example 5

[0059] A method for preparing a NiCoCu selenide composite MXene / carbon sphere thin film electrode material comprises the following steps:

[0060] Step 1, weigh 3mmol Co(NO3)2·6H2O and 1.633g 2-methylimidazole and dissolve them in 20mL methanol respectively, mix the Co(NO3)2 methanol solution and the 2-methylimidazole solution and stir for 10 minutes, place at room temperature for 24 hours, centrifuge, and dry at 60°C to obtain ZIF-67 powder; weigh 4g glucose and dissolve it in 40mL deionized water, and hydrothermally react at 160°C for 6h to obtain a carbon ball solution; take 50mg of the above ZIF-67 powder and dissolve it in 20mL carbon ball solution, then add 5mL MXene aqueous solution, stir at room temperature for 6h, filter and dry to obtain ZIF-67@MXene / CS;

[0061] Step 2, weigh 0.3g CO(NH2)2, 0.3mmol Cu(NO3)2·3H2O, 0.3mmol Ni(NO3)2·6H2O and dissolve them in 20mL ethanol, immerse the prepared ZIF-67@MXene / CS film in the above solution, and react at 120℃ for 1h; after the reactor is cooled to room temperature, take out the sample, wash the sample with deionized water and anhydrous ethanol several times, and dry it at 60℃ to obtain NiCoCu-LDH@MXene / CS film;

[0062] Step 3: NiCoCu-LDH@MXene / CS, selenium powder and sodium borohydride were mixed in a mass ratio of 1:1:2 in an autoclave and reacted at 180°C for 24 hours. The obtained material was washed with deionized water and dried to obtain NiCoCu-Se@MXene / CS.

[0063] The prepared NiCoCu-Se@MXene / CS composite thin film electrode material was used as the positive electrode material of the supercapacitor for a cycle stability test. The capacity retention rate was 77.1% after 10,000 cycles, showing good cycle performance.

[0064] Example 6

[0065] A method for preparing a NiCoCu selenide composite MXene / carbon sphere thin film electrode material comprises the following steps:

[0066] Step 1, weigh 3mmol Co(NO3)2·6H2O and 1.633g 2-methylimidazole and dissolve them in 20mL methanol respectively, mix the Co(NO3)2 methanol solution and the 2-methylimidazole solution and stir for 10 minutes, place at room temperature for 24 hours, centrifuge, and dry at 60°C to obtain ZIF-67 powder; weigh 4g glucose and dissolve it in 40mL deionized water, and hydrothermally react at 160°C for 6h to obtain a carbon ball solution; take 50mg of the above ZIF-67 powder and dissolve it in 20mL carbon ball solution, then add 5mL MXene aqueous solution, stir at room temperature for 6h, filter and dry to obtain ZIF-67@MXene / CS;

[0067] Step 2: Weigh 0.3 g CO(NH2)2, 0.3 mmol Cu(NO3)2·3H2O, and 0.3 mmol Ni(NO3)2·6H2O and dissolve them in 20 mL ethanol. Immerse the prepared ZIF-67@MXene / CS film in the above solution and react at 120°C for 2 h. After the reactor is cooled to room temperature, take out the sample, wash the sample with deionized water and anhydrous ethanol several times, and dry it at 60°C to obtain NiCoCu-LDH@MXene / CS film.

[0068] Step 3: NiCoCu-LDH@MXene / CS, selenium powder and sodium borohydride were mixed in an autoclave at a mass ratio of 0.5:2:2 and reacted at 180°C for 24 hours. The obtained material was washed with deionized water and dried to obtain NiCoCu-Se@MXene / CS.

[0069] The prepared NiCoCu-Se@MXene / CS composite thin film electrode material was used as the positive electrode material of the supercapacitor for a cycle stability test. The capacity retention rate was 76.5% after 10,000 cycles, showing good cycle performance.

[0070] Example 7

[0071] A method for preparing a NiCoCu selenide composite MXene / carbon sphere thin film electrode material comprises the following steps:

[0072] Step 1, weigh 3mmol Co(NO3)2·6H2O and 1.633g 2-methylimidazole and dissolve them in 20mL methanol respectively, mix the Co(NO3)2 methanol solution and the 2-methylimidazole solution and stir for 10 minutes, place at room temperature for 24 hours, centrifuge, and dry at 60°C to obtain ZIF-67 powder; weigh 4g glucose and dissolve it in 40mL deionized water, and hydrothermally react at 160°C for 6h to obtain a carbon ball solution; take 50mg of the above ZIF-67 powder and dissolve it in 20mL carbon ball solution, then add 5mL MXene aqueous solution, stir at room temperature for 6h, filter and dry to obtain ZIF-67@MXene / CS;

[0073] Step 2, weigh 0.3g CO(NH2)2, 0.3mmol Cu(NO3)2·3H2O, 0.3mmol Ni(NO3)2·6H2O and dissolve them in 20mL ethanol, immerse the prepared ZIF-67@MXene / CS film in the above solution, and react at 120℃ for 2h; after the reactor is cooled to room temperature, take out the sample, wash the sample with deionized water and anhydrous ethanol several times, and dry it at 60℃ to obtain NiCoCu-LDH@MXene / CS film;

[0074] Step 3: NiCoCu-LDH@MXene / CS, selenium powder and sodium borohydride were mixed in a mass ratio of 1:1:1 in an autoclave and reacted at 180°C for 24 hours. The obtained material was washed with deionized water and dried to obtain NiCoCu-Se@MXene / CS.

[0075] The prepared NiCoCu-Se@MXene / CS composite thin film electrode material was used as the positive electrode material of the supercapacitor for a cycle stability test. The capacity retention rate was 72.4% after 10,000 cycles, showing good cycle performance.

[0076] Example 8

[0077] A method for preparing a NiCoCu selenide composite MXene / carbon sphere thin film electrode material comprises the following steps:

[0078] Step 1, weigh 3mmol Co(NO3)2·6H2O and 1.633g 2-methylimidazole and dissolve them in 20mL methanol respectively, mix the Co(NO3)2 methanol solution and the 2-methylimidazole solution and stir for 10 minutes, place at room temperature for 24 hours, centrifuge, and dry at 60°C to obtain ZIF-67 powder; weigh 4g glucose and dissolve it in 40mL deionized water, and hydrothermally react at 160°C for 6h to obtain a carbon ball solution; take 50mg of the above ZIF-67 powder and dissolve it in 20mL carbon ball solution, then add 5mL MXene aqueous solution, stir at room temperature for 6h, filter and dry to obtain ZIF-67@MXene / CS;

[0079] Step 2: Weigh 0.3 g CO(NH2)2, 0.3 mmol Cu(NO3)2·3H2O, and 0.3 mmol Ni(NO3)2·6H2O and dissolve them in 20 mL ethanol. Immerse the prepared ZIF-67@MXene / CS film in the above solution and react at 120°C for 2 h. After the reactor cools to room temperature, take out the sample, wash the sample with deionized water and anhydrous ethanol several times, and dry it at 60°C to obtain NiCoCu-LDH@MXene / CS film.

[0080] Step 3: NiCoCu-LDH@MXene / CS, selenium powder and sodium borohydride were mixed in a mass ratio of 1:1:2 in an autoclave and reacted at 150°C for 24 hours. The obtained material was washed with deionized water and dried to obtain NiCoCu-Se@MXene / CS.

[0081] The prepared NiCoCu-Se@MXene / CS composite thin film electrode material was used as the positive electrode material of the supercapacitor for a cycle stability test. The capacity retention rate was 70.1% after 10,000 cycles, showing good cycle performance.

[0082] Example 9

[0083] A method for preparing a NiCoCu selenide composite MXene / carbon sphere thin film electrode material comprises the following steps:

[0084] Step 1, weigh 3mmol Co(NO3)2·6H2O and 1.633g 2-methylimidazole and dissolve them in 20mL methanol respectively, mix the Co(NO3)2 methanol solution and the 2-methylimidazole solution and stir for 10 minutes, place at room temperature for 24 hours, centrifuge, and dry at 60°C to obtain ZIF-67 powder; weigh 4g glucose and dissolve it in 40mL deionized water, and hydrothermally react at 160°C for 6h to obtain a carbon ball solution; take 50mg of the above ZIF-67 powder and dissolve it in 20mL carbon ball solution, then add 5mL MXene aqueous solution, stir at room temperature for 6h, filter and dry to obtain ZIF-67@MXene / CS;

[0085] Step 2, weigh 0.3g CO(NH2)2, 0.3mmol Cu(NO3)2·3H2O, 0.3mmol Ni(NO3)2·6H2O and dissolve them in 20mL ethanol, immerse the prepared ZIF-67@MXene / CS film in the above solution, and react at 120℃ for 2h; after the reactor is cooled to room temperature, take out the sample, wash the sample with deionized water and anhydrous ethanol several times, and dry it at 60℃ to obtain NiCoCu-LDH@MXene / CS film;

[0086] Step 3: NiCoCu-LDH@MXene / CS, selenium powder and sodium borohydride were mixed in a mass ratio of 1:1:2 in an autoclave and reacted at 180°C for 12 hours. The obtained material was washed with deionized water and dried to obtain NiCoCu-Se@MXene / CS.

[0087] The prepared NiCoCu-Se@MXene / CS composite thin film electrode material was used as the positive electrode material of the supercapacitor for a cycle stability test. The capacity retention rate was 71.6% after 10,000 cycles, showing good cycle performance.

[0088] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a NiCoCu selenide composite MXene / carbon sphere thin film electrode material, characterized in that: The following steps are involved: A. Dissolve ZIF-67 powder in carbon sphere solution, add MXene aqueous solution, stir for 1-10 hours, filter and dry to obtain ZIF-67@MXene / CS; wherein the material ratio of ZIF-67 powder, carbon sphere solution and MXene aqueous solution is 10-80 mg: 10-30 mL: 2-10 mL; B. Prepare a solution according to the material ratio of urea, copper source, nickel source and ethanol of 0.1-0.6g: 0.1-0.5mM: 0.1-0.5mM: 15-30mL, preferably 0.3g: 0.3mM: 0.3mM: 20mL; immerse the above ZIF-67@MXene / CS, react at 100-120°C for 1-2h, preferably at 120°C for 2h, take out the reactor after it is naturally cooled to room temperature, wash it with deionized water and anhydrous ethanol several times, and dry it at 60°C to obtain a NiCoCu-LDH@MXene / CS film; C. NiCoCu-LDH@MXene / CS film, selenium powder and sodium borohydride are mixed in a mass ratio of 0.5~1:1~2:1~2, preferably 1:1:2, and reacted in an autoclave at 150~180°C for 12~24 h, preferably at 180°C for 24 h. The obtained product is washed with deionized water and dried.

2. The method for preparing the NiCoCu selenide composite MXene / carbon sphere thin film electrode material according to claim 1, characterized in that: In step A, the ZIF-67 powder is dissolved in the carbon sphere solution, and then the MXene aqueous solution is added, stirred for 6 hours, filtered and dried to obtain ZIF-67@MXene / CS; wherein the material ratio of the ZIF-67 powder, the carbon sphere solution and the MXene aqueous solution is 50 mg: 20 mL: 5 mL.

3. The method for preparing the NiCoCu selenide composite MXene / carbon sphere thin film electrode material according to claim 1, characterized in that: In step A, the ZIF-67 powder is obtained by mixing equal volumes of a cobalt salt-methanol solution and a 2-methylimidazole-methanol solution, stirring the mixture evenly, centrifuging the mixture after standing for 24 hours, and drying the mixture at 60° C., wherein the cobalt salt is Co(NO3)2 or CoCl2.

4. The method for preparing the NiCoCu selenide composite MXene / carbon sphere thin film electrode material according to claim 3, characterized in that: In step A, the cobalt salt-methanol solution is a mixture of cobalt salt and methanol at a ratio of 1 to 5 mmol: 15 to 30 mL, preferably 3 mmol: 20 mL; the 2-methylimidazole-methanol solution is a mixture of 2-methylimidazole: methanol at a material ratio of 0.820 to 2.46 g: 15 to 30 mL, preferably 1.633 g: 20 mL.

5. The method for preparing the NiCoCu selenide composite MXene / carbon sphere thin film electrode material according to claim 1, characterized in that: In step A, the carbon ball solution is prepared by dissolving the carbon source in deionized water at a ratio of 3-5 g: 20-50 mL, preferably 4 g: 40 mL, and hydrothermally reacting at 150-180° C. for 4-8 h, preferably at 160° C. for 6 h, wherein the carbon source is glucose.

6. The method for preparing the NiCoCu selenide composite MXene / carbon sphere thin film electrode material according to claim 1, characterized in that: In step A, the MXene aqueous solution is a titanium carbide aqueous solution with a concentration of 4.5 mg / mL.

7. The method for preparing the NiCoCu selenide composite MXene / carbon sphere thin film electrode material according to claim 1, characterized in that: In step B, the copper source is Cu(NO3)2 or CuSO4, preferably Cu(NO3)2; the nickel source is Ni(NO3)2 or NiCl2, preferably Ni(NO3)2.

8. The NiCoCu selenide composite MXene / carbon ball thin film electrode material prepared according to any one of claims 1 to 7.

9. The NiCoCu selenide composite MXene / carbon ball thin film electrode material according to claim 8, characterized in that: Its microscopic morphology is that NiCoCu-Se polyhedron is composited with MXene / CS, and the polyhedron appears hollow.

10. An application of the NiCoCu selenide composite MXene / carbon ball thin film electrode material as claimed in claim 8 or 9, characterized in that: It is applied to positive electrode materials of supercapacitors.

Citation Information

Patent Citations

  • Preparation and application methods of nanometer carbon sphere-supported MXene composite material

    CN109449402A

  • Nickel cobalt selenide / carbon composite material and preparation method and application thereof

    CN113299486A

  • Carbon hollow sphere coated metal selenide composite material as well as preparation method and application thereof

    CN114464465A

  • Preparation method of bimetallic CoZn-Se-MXene electrode

    CN115528227A

  • Preparation method of carbon / copper sulfide / MXene composite electrode material

    CN115985694A

Cited By

  • Three-dimensional multilayer LDH / CS / PPy composite material and preparation method and application thereof

    CN121983433A